Prototyping a dual-channel receiver for use in a staring cooperative radar network for the detection of drones - Griffin, Benjamin; Balleri, Alessio; Baker, Chris J.; Jahangir, Mohammed (IEEE, 2021)
Staring radars use a transmitting static wide-beam antenna and a directive digital array to form multiple simultaneous beams on receive. Because beams are fixed, the radar can employ long integration times to detect slow low-RCS targets, such as drones, which present a challenge to traditional air surveillance radar. The use of multiple spatially separated receivers cooperating with the staring transmitters in a multistatic network allows multi-perspective target acquisitions that can help mitigate interference, such as signal multipath, and ultimately enhance the detection of drones and reduce target parameter estimation errors. Here, the design of a dual-channel receiver prototype for use in a multistatic cooperative network is presented. Several measurements have been taken using the prototype receiver in a bistatic configuration to test and assess its performance.
Keywords: Receivers; Rotors; Prototypes; Radar detection; Helicopters; Surveillance; Radar measurements